Improving Football Dribbling Learning Outcomes Through the Teams Games Tournament (TGT) Cooperative Learning Model for Class V Students at SDN Paya Deman 2 - Ratnawati (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The general objective of this research is to enhance student outcomes through the implementation of soccer dribbling using the cooperative model of Teams Games Tournament (TGT). Additionally, this study aims to obtain in-depth information about the application of game variations in soccer dribbling. The research design employed is Classroom Action Research (CAR). The subjects in this study are 22 students from class V at SDN Paya Demam 2. The research was conducted over two meetings spanning two cycles. Each cycle consisted of four stages. The first cycle indicated that through action, students can self-motivate. From this first cycle, the result was 46%, indicating it was incomplete. The second cycle, as a reflection of the first cycle, also demonstrated that action improves student learning outcomes. The result of the second cycle was 100%, indicating completion. Based on the findings of this research, it can be concluded that: (1) Learning soccer dribbling using the cooperative model of Teams Games Tournament (TGT) enhances student learning outcomes, (2) Learning soccer dribbling using TGT motivates students and encourages active participation in the learning process.